Dendrobium officinale-derived nanovesicles: a natural therapy for comprehensive regulation of angiogenesis, inflammation, and tissue repair to enhance skin wound healing - Jin Tu; Luhua Xu; Yuqin Guo; Minzhi Zhang; Miao Gan; Xiuzhen Bao; Rongfeng Yang; Hanjiao Liu; Fengxia Lin (Bioresources and Bioprocessing)
Abstract Skin wound healing is a multifaceted biological process involving dynamic interactions among various cells and signaling molecules. Angiogenesis is a key component of this repair process. Dendrobium officinale, a traditional medicinal plant, has shown therapeutic promise, particularly through its bioactive nanovesicles. This study investigates the therapeutic potential of Dendrobium officinale-derived nanovesicles (DDNVs) in regulating angiogenesis, inflammation, and tissue repair, to promote enhanced skin wound healing. A full-thickness mouse skin wound model was used to evaluate the in vivo effects of DDNVs on wound closure, angiogenesis, and collagen remodeling. Histological staining (H&E and Masson’s trichrome) and CD31 immunofluorescence were performed. In vitro, DDNVs were tested on Human umbilical vein endothelial cells(HUVECs) and Human keratinocyte cells (HaCaT) cells to assess cell proliferation, migration, and angiogenesis. Confocal microscopy was used to track cellular uptake. Activation of the Akt/eNOS pathway and expression of key genes related to inflammation and matrix remodeling were evaluated by Western blotting and qPCR. DDNVs significantly accelerated wound healing and promoted angiogenesis in vivo, as evidenced by enhanced CD31 expression and collagen remodeling. In vitro, DDNVs entered cells efficiently and stimulated HUVEC and HaCaT proliferation and migration. This was accompanied by activation of the Akt/eNOS signaling pathway, increased expression of eNOS and VEGFR-2, upregulation of extracellular matrix(ECM) components (Vimentin, Fibronectin, COL1A1), and suppression of inflammatory markers such as ICAM-1 and IL-1β. DDNVs exhibit strong potential to enhance skin wound healing by promoting angiogenesis, improving tissue repair, and modulating inflammation. These findings support the clinical development of DDNVs as a novel, plant-derived nanotherapeutic for chronic wound treatment and skin regeneration.